Britain and the Cyprus Crisis of 1974 - Burke, John (John Edward), 1987-, author.
1 online resource (viii, 117 pages)
Keywords: "This book examines the ideological and socio-political discourses shaping the remembrance and representation of Britain and the Cyprus conflict of 1974 within Greek Cypriot society. By combining the official to the popular, and drawing on an extensive range of oral history interviews, this monograph shows that a suspicion born out of Britain's long (neo)-colonial connection towards Cyprus has come to frame the image and understanding of British actions associated with the events, and lasting consequences, of 1974. Indeed, with the island of Cyprus still divided, and the requirement to remember a national imperative, this book has a direct contemporary relevance. However within the existent literature, whilst much has been written about the political roots of the Cyprus conflict, no study has yet sought to systematically analyse and understand the influences shaping the history and memory of British actions on Cyprus in 1974. One defined by the existence of 'partitionist' conspiracies, collusive accusations, and a series of memory distortions which continue to resonate strongly irrespective of the evidence which is now available. As such, by analysing the influences shaping the image of Britain in 1974, one can begin to understand in ever greater detail the Anglo-Greek Cypriot relationship in a modern context. John Burke is a teacher at Newcastle University, UK"--Provided by publisher.